Science Technology Engineering and Mathematics (STEM) Education Approach against a Microscopic Representation Skill in Atom and Molecule Concept - Asih Widi Wisudawati (International Journal of Chemistry Education Research, 2018)
ABSTRACT: The aim of this research in to know microscopic representation change in atom and molecule concept which is influenced by STEM Education. This research is one of the sequences in Research and Development of test instrument by chemistry software. The kind of this research is fieldwork research with one group pre-test and post-test design. Subjects in this research are the twenty-seven  students in MBS Senior High School grade 11 th in Yogyakarta region. STEM Education can improve student microscopic representation skill from 30.18 to 54.62 in average score and based on student result in painting molecule with ChemDraw and Avogadro's application, there are a lot of improvement in understanding concept.Keywords: STEM education, microscopics representations, atom and moleculeReceived: 11 January 2018, Revised: 21 January 2018, Accepted: 24 February 2018